As transformações no mundo do trabalho e as implicações na formação dos pescadores artesanais na Amazônia tocantina - BARRA, José Domingos Fernandes (Universidade Federal do Pará, 2019)
This thesis examines the transformations of the world of work and its implications for the training of artisanal fishermen in the municipality of Cametá, on the banks of the Tocantins River in the state of Pará. It is a work that shows the changes that have changed the life of the fisherman. The reconfiguration of their life dynamics and the strategies adopted for these fishermen to form, faced with the demands of the contemporary world, from the various forms of interaction that are established in the work in relation to the river. This is a qualitative research that uses the case study. To carry out this research, a bibliographic survey was carried out on the ground in the bordering communities of the Amazon tocantina, in particular in the communities of Rio Ovidio and Joroca de baixo, in the municipality of Cametá, where interviews were conducted. semi-structured questionnaires and participant observation. We process informant statements via content analysis. Among the categories of work, training and qualification, we seek the theoretical orientation of research in Marx (2008), Gramsci (1987, 1988, 2006), Antunes (2003, 2006, 2009, 2013), Diegues (2015), Marx and Engels (2006, 2007), among others. The analyzes led to investigations of what is expected of working in a peripheral territory, in a peripheral Amazonia. It was also important to realize that in this world of work, artisanal fishermen are “framed” in a unilateral perspective, based on the logic of global capitalism, where rural territories are invisible in the field of artisanal fisheries. On the other hand, it is possible to highlight the resistance, the forms that these fishermen have sought to confront in the world of work, since the human formation in the Christian communities and the Prelature of Cametá and, consecutively, in the logic social movements, referring to the Cametá Z-16 fishing colony, which has influenced the constitutive process or the production of knowledge or forms of participation and has, through a dialectical process, redefined their knowledge by adapting social practices and economic. There have been changes in the world of work that have resulted in the process of establishing the artisanal fisherman, because the world of work is in contradiction with the changes made to the fishing territories, while giving access to the necessary consumer goods, lifestyle with quality; combined with this, conviviality with environmental problems, intensified by the practice of work, by the cultural actions coming from the capital, generated conflicts, migrations and a proletarianization of the fisherman